Impact of Zeolite Aging in Hot Liquid Water on Activity for Acid-Catalyzed Dehydration of Alcohols - Vjunov, Aleksei; Derewinski, Miroslaw A; Fulton, John L; Camaioni, Donald M; Lercher, Johannes A (Journal of the American Chemical Society, 2015)
The location and stability of Brønsted acid sites catalytically active in zeolites during aqueous phase dehydration of alcohols were studied on the example of cyclohexanol. The catalytically active hydronium ions originate from Brønsted acid sites (BAS) of the zeolite that are formed by framework tetrahedral Si atom substitution by Al. Al K-edge extended X-ray absorption fine structure (EXAFS) and 27Al magic angle spinning (MAS) nuclear magnetic resonance (NMR) spectroscopies in combination with density functional theory (DFT) calculations are used to determine the distribution of tetrahedral Al sites (Al T-sites) both qualitatively and quantitatively for both parent and HBEA catalysts aged in water prior to catalytic testing. The aging procedure leads to partial degradation of the zeolite framework evidenced from the decrease of material crystallinity (XRD) as well as sorption capacity (BET). With the exception of one commercial zeolite sample, which had the highest concentration of framework silanol-defects, there is no evidence of Al coordination modification after aging in water. The catalyst weight-normalized dehydration rate correlated best with the sum of strong and weak Brønsted acidic protons both able to generate the hydrated hydronium ions. All hydronium ions were equally active for the acid-catalyzed reactions in water. Zeolite aging in hot water prior to catalysis decreased the weight normalized dehydration reaction rate compared to that of the parent HBEA, which is attributed to the reduced concentration of accessible Brønsted acid sites. Sites are hypothesized to be blocked due to reprecipitation of silica dissolved during framework hydrolysis in the aging procedure.